2021
DOI: 10.1589/jpts.33.394
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone addiction and its association with upper body musculoskeletal symptoms among university students classified by age and gender

Abstract: The purposes of this study were to: 1) survey smartphone addiction among university students, 2) survey the prevalence of upper body musculoskeletal symptoms in relation to the respondents' sitting posture, and 3) determine the association between smartphone addiction and upper body musculoskeletal symptoms, classified by age and gender. [Participants and Methods] Two self-report questionnaires were employed to collect data from 2,645 university students in Chiang Mai, Thailand. [Results] Of 2,027 respondents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…The findings of this study revealed that musculoskeletal symptoms in the shoulder, elbow, and wrist/hand region were associated with smartphone addiction/overuse and are consistent with earlier research among similar populations [ 33 , 50 , 51 ]. Individuals who were categorized as experiencing smartphone overuse/addiction adopt faulty postures, as their necks are flexed and their elbows are unsupported during extensive use of their smartphones, resulting in profuse static load in the neck and upper extremities [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study revealed that musculoskeletal symptoms in the shoulder, elbow, and wrist/hand region were associated with smartphone addiction/overuse and are consistent with earlier research among similar populations [ 33 , 50 , 51 ]. Individuals who were categorized as experiencing smartphone overuse/addiction adopt faulty postures, as their necks are flexed and their elbows are unsupported during extensive use of their smartphones, resulting in profuse static load in the neck and upper extremities [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…For an example, a recent study conducted in Saudi Arabia reported that youth was a strong predictor of SA [ 12 ]. Several studies also suggested that that SA was associated with different physical problems like insomnia [ 15 ], musculoskeletal problems [ 16 ] and low levels of physical activity [ 17 ]. A study conducted among Korean adults found that cervical repositioning errors were associated with SA [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that older people tend to have greater complaints, especially in the neck area, and the duration of use also contributes. [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%